Edukasi tentang Pentingnya Konsumsi Sayur dan Buah Setiap Hari pada Anak di SDN 069 Lanrae Kabupaten Polewali Mandar: Edukasi tentang Pentingnya Konsumsi Sayur dan Buah Setiap Hari pada Anakdi SDN 069 Lanrae Kabupaten Polewali Mandar - Putri, Sri Agusty; Rasmawati; Sebba, Ade Kartikasari; Harma, Sitti; Haerani; Febrianty, Femi; Ofan, Hilky (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2025)
Globally, vegetable and fruit consumption among children remains relatively low, and this is also the case in Lanrae Hamlet, as many children fail to meet the recommended nutritional intake based on balanced nutrition. The goal of this community service (PkM) activity is to increase knowledge among elementary school students by educating them about the importance of daily vegetable and fruit consumption at Elementary School 069 Lanrae in Polewali Mandar Regency.The education provided uses leaflets to make it easier for children to understand the information they receive about the importance of consuming vegetables and fruits every day. Participants in this PkM activity were 26 fourth-grade students. To determine student understanding, knowledge was measured before and after the education. The results obtained showed a significant increase in students' knowledge, namely, before education, there were 80.8% of students who had poor knowledge, and after education there was an increase of 96.2% of students who had good knowledge about the importance of consuming vegetables and fruit every day. Thus, it is hoped that this education will have an impact on children's food consumption patterns, fostering good habits of consuming vegetables and fruits every day from an early age, which will provide health benefits in every cycle of life.